Pengaruh Penambahan Bubuk Kulit Delima terhadap Rheology dan Filtration Loss Lumpur Pemboran - Carlos Tulak; Nuruddin Kafy El Ridlo; M Nur Mukmin (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Drilling mud plays a vital role in ensuring the continuity, efficiency, and safety of drilling operations. However, conventional additives such as bentonite and barite are generally derived from mined materials, resulting in relatively high operational costs. This study aims to investigate the potential of pomegranate (Punica granatum) peel powder as an alternative natural additive that is inexpensive and readily available, with particular emphasis on its effects on the rheological properties and filtration loss of water-based drilling mud. Laboratory experiments were conducted using pomegranate peel powder concentrations of 1, 3, 5, and 7 g, following the testing procedures recommended by Fann Instrument Company. The results indicate that the addition of pomegranate peel powder consistently increased plastic viscosity, yield point, gel strength, and mud weight, while simultaneously reducing filtration loss and mud pH as the concentration increased. All measured parameters remained within the specifications of the API 13A standard, indicating that pomegranate peel powder has strong potential as an economical and environmentally friendly drilling mud additive.